CAUSE FACTORS SYMBOLIC RESISTANCE OF GRAPHIC DESIGNERS IN DENPASAR CITY - I Ketut Sutarwiyasa; I Nyoman Darma Putra; A.A. Ngurah Anom Kumbara; Ni Made Wiasti (E-Journal of Cultural Studies, 2021)
The discourse of "free design" that was introduced by printing companies as a form of strategy in dealing with business competition, has caused controversy in the graphic design field. Indirectly, this discourse is considered to be able to influence the mindset of the community and become a negative stigma against the graphic designer profession, and the discourse is considered to be a threat to the continuity of the graphic designer profession.This study aims to answer the factors that cause resistance. The study data were taken from observation, social media, and interviews, and analyzed using Michel Foucault's power relation theory and Norman Fairclough's theory of critical discourse analysis. Keywords: hidden transcripts, symbolic resistance, graphic designer, free design